THE CONSTRUCT «READING LITERACY»: AN ATTEMPT TO EXPLAIN IN TERMS OF PSYCHOLOGY - Dieorditsa, Taiana; Gladushyna, Raisa; Voronina, Maryna; Tolmachov, Volodimir (Physical and Mathematical Education, 2025)
Formulation of the Problem. Based on our observations, Ukrainian researchers, when studying the abstract concept of «reading literacy», tend to focus exclusively on its dictionary definition, while ignoring the operational one. However, the operational definition provides clarity and measurability to this abstraction. In addition, In Ukrainian pedagogical journals, we did not find any publications that explain the existence of two approaches to assessment reading literacy levels – in the PIRLS and PISA studies. Given this omission, we posed the following questions: (1) How are reading literacy levels measured in PIRLS and PISA? (2) What factors influenced the creation of this abstraction? Materials and Methods. As followers of the psychological theory of activity, we sought to answer the first question of our investigation from its perspective. To this end, we analyzed several framework documents from PIRLS and PISA published in different years, including PIRLS 2026 Assessment Frameworks (von Davier & Kennedy, 2024), Measuring Student Knowledge and Skills: The PISA 2000 (OECD, 2000), PISA 2009 Assessment Framework: Key Competencies in Reading, Mathematics, and Science (OECD, 2009), and PISA 2018 Assessment Analytical Framework (OECD, 2019). To answer the second question, we used the retrospective analysis of previous evaluative studies on students’ reading achievements. Results. It has been established that «reading literacy» is a psychological construct designed to serve as a theoretical basis for developing reliable psychometric tests for measuring student achievement in reading. The logic of the operationalization of this construct has been clarified. In connection with the psychological theory of activity, its measurable indicators are intellectual operations that implement three key intellectual actions of reading activity: reviewing the text; understanding, and evaluating what has been read. In the PIRLS, the intensity of manifestation of four such operations is measured in PISA – seven. This is quite acceptable, given that the operational composition of the action depends on the conditions of its execution. The testing conditions for the PIRLS and PISA are different because their participants belong to various age groups. It has been revealed that the creation of the construct «reading literacy» was influenced by the researchers’ rethinking of the forms of manifestation of the construct «reading comprehension» – as a process and a product. Conclusion. Following the logic of Alfred Korzybski’s axiom, «the map is not the territory,» we find it reasonable to state that reading literacy is not reading. Reading is a cognitive activity while reading literacy is merely a measure of proficiency in this activity. Given this distinction, the operational definitions of the construct «reading literacy,» proposed in PIRLS and PISA, can be considered as verified samples of cognitive operations, the mastering of which will help students to read consciously.